Teori Perkembangan Anak dan Teori Belajar sebagai Landasan Psikologis Pendidikan Dasar: Implikasi terhadap Praktik Pembelajaran di Sekolah Dasar - Diana Syahfitri; Devika Sri Yunda; Syofiani; Rieke Alyusfitri (STKIP Subang, 2026)
Elementary education plays a fundamental role in shaping students’ cognitive, social, and emotional development. Therefore, the learning process in elementary schools should be grounded in strong psychological foundations, particularly child development theories and learning theories. This article aims to analyze child development theories and learning theories as psychological foundations of elementary education and their implications for instructional practices in elementary schools. This study employed a qualitative approach using library research. Data were obtained from educational psychology textbooks, child development theory books, learning theory references, and relevant scholarly journal articles. Data analysis was conducted through content analysis of the selected literature. The findings indicate that child development theories proposed by Piaget, Erikson, and Vygotsky provide a comprehensive understanding of elementary school students’ characteristics in terms of cognitive, psychosocial, and socio-cultural aspects. Meanwhile, behaviorist, cognitive, constructivist, and humanistic learning theories offer a conceptual framework for teachers in designing learning activities that are appropriate to students’ developmental stages and learning needs. The implications of this study emphasize the importance of the teacher’s role as a learning facilitator, the adjustment of instructional methods, media, and assessment, the implementation of student-centered learning, and the creation of a learning environment that supports children’s development. Thus, integrating child development theories and learning theories as psychological foundations of elementary education is expected to promote effective, meaningful, and developmentally appropriate learning